Directing peptide crystallization through curvature control of nanotubes‡. (11th June 2014) - Gobeaux, Frédéric; Tarabout, Christophe; Fay, Nicolas; Meriadec, Cristelle; Ligeti, Melinda; Buisson, David‐Alexandre; Cintrat, Jean‐Christophe; Artzner, Franck; Paternostre, Maïté; Morelli, Giancarlo; Toniolo, Claudio; Venanzi, Mariano
<x xml:space="preserve">Abstract</x> In the absence of efficient crystallization methods, the molecular structures of fibrous assemblies have so far remained rather elusive. In this paper, we present a rational method to crystallize the lanreotide octapeptide by modification of a residue involved in a close contact. Indeed, we show that it is possible to modify the curvature of the lanreotide nanotubes and hence their diameter. This fine tuning leads to crystallization because the radius of curvature of the initially bidimensional peptide wall can be increased up to a point where the wall is essentially flat and a crystal is allowed to grow along a third dimension. By comparing X‐ray diffraction data and Fourier transform Raman spectra, we show that the nanotubes and the crystals share similar cell parameters and molecular conformations, proving that there is indeed a structural continuum between these two morphologies. These results illustrate a novel approach to crystallization and represent the first step towards the acquisition of an Å‐resolution structure of the lanreotide nanotubes β‐sheet assembly. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.